Autoimmune mediated neuromuscular junction defects. - Farrugia, M; Vincent, A (2010)
PURPOSE OF REVIEW: This review summarizes the recent advances on pathogenesis of antibody-mediated disorders of the neuromuscular junction, and results of studies on clinical assessment and treatments. RECENT FINDINGS: The incidence of myasthenia gravis, particularly in patients older than 50 years, is rising, and this is not solely due to improved disease recognition. It is uncertain how muscle specific tyrosine kinase (MuSK) antibody positive myasthenia gravis results in neuromuscular transmission failure since MuSK antibodies alter neuromuscular junction morphology without altering acetylcholine receptor numbers or turnover. Clinical tools have been developed that allow rapid and reliable disease assessment. The myasthenia gravis composite score addresses items commonly affected in myasthenia gravis, is sensitive to detect clinical change and helps guide the physician in therapy prescription. Immunosuppression remains the mainstay of myasthenia gravis treatment. Other therapies, such as rituximab, are increasingly prescribed for refractory myasthenia gravis, and drugs that inhibit complement are being explored in myasthenia gravis and Guillain-Barré syndrome (GBS). In Lambert-Eaton myasthenic syndrome (LEMS), SOX antibodies help distinguish between tumour and nontumour LEMS. Ganglioside complexes in GBS and Miller-Fisher syndrome are frequently present and are more pathogenic. SUMMARY: Developments in serological assays, particularly of cell-based assays, are continuing to improve the diagnosis and investigation of these conditions. Learning more on pathogenicity has helped us to apply newer therapies.